The global economic and financial crisis and the Jamaican bauxite and alumina industry - Davis, Carlton E. ([ILO-SRO] [Port of Spain]TT, 2009)
Focuses on the contributions of the industry to the Jamaican economy; the challenges it faces; the current situation; and, the way forward.